Prevention of illegal crossing of State Border of Ukraine by persons of conscript age for purpose of evading conviction for military service during mobilization - Hanba, Oleh; Radchenia, Nataliia; Ivashkova, Tetiana (Migration & Law, 2025)
The scientific article highlights the problematic aspects of preventing illegal crossing of the state border of Ukraine by citizens of draft age in order to evade conscription for military service during mobilization. The results of the operational and service activities of the State Border Guard Service of Ukraine for 2023 and 2024 are highlighted and the results of sociological surveys on the study of public opinion on evasion of conscription for military service during mobilization are characterized. The system of qualitative prevention of illegal crossing of the state border of Ukraine by individuals in order to evade conscription for military service during mobilization is characterized, within which three components are distinguished: identification, analysis and neutralization of the motives that prompted the subject of the offense to commit it; determination of the circle of subjects who commit the specified offenses or contribute to their commission; identification of preventive measures already applied by the State Border Guard Service of Ukraine, and a proposal to take new effective measures caused by the needs of such prevention in the conditions of martial law and large-scale aggression of the Russian Federation. The mechanism of evasion of a person from conscription for military service during mobilization is outlined with a specification of its stages. Effective preventive measures have been identified by the personnel of the State Border Guard Service of Ukraine to prevent illegal crossing of the state border of Ukraine by persons in order to evade conscription for military service during mobilization, which have been tested by the personnel of the bodies and units of the state border protection, as well as proposed by scientists and competent practical specialists of the State Border Guard Service of Ukraine and other law enforcement agencies.
Keywords: Prevention of offences; Crime; Administrative offence; Protection of State Border; State Border Guard Service of Ukraine; Evasion of conscription; Mobilisation